Solutions to cultural, organizational, and technical challenges in developing PECAS models for the cities of Shanghai, Wuhan, and Guangzhou - Zhong, Ming; Wang, Wanle; Hunt, John Douglas; Pan, Haixiao; Chen, Tao; Li, Jianzhong; Yang, Wei; Zhang, Ke (Journal of Transport and Land Use, 2018)
Massive construction of transportation infrastructure and fast growth of private car ownership have brought unprecedented changes in land use and transportation systems to cities and regions in many developing countries. Traditional “four-step” travel demand models, which are not designed to assess transport policies under the case of rapid land-use change, cannot be used to achieve coordinated planning of transport and land use. Therefore, there is a pressing need to develop and use integrated land-use transport models (ILUTMs), which consider interactions among socioeconomic activities, urban land use, and transportation development, for policy analysis and for guiding the progressive urbanization process taking place in many parts of these countries. In light of this, efforts have been invested in developing production, exchange, and consumption allocation system (PECAS) models for the cities of Shanghai, Wuhan, and Guangzhou in mainland China. This paper presents the cultural, organizational, and technical challenges encountered in the development of PECAS models for the cities of Shanghai, Wuhan, and Guangzhou and the mitigating solutions from the development teams for taking up or working around them. The solutions and discussions presented in this paper should be interesting to researchers and practitioners for developing ILUTMs in the context of a developing country like China.